Disparitas Putusan Hakim dalam Kasus Kekerasan Seksual oleh Pelaku Anak - Ali, Nurul Fatwa; Sunariyo, Sunariyo; Alhadi, Muhammad Nurcholis (Universitas Muhammadiyah Ponorogo, 2025)
Crimes against children are increasingly occurring, especially sexual violence that does not only recognize place and time, but also does not recognize who will be the perpetrator and victim. For example, the child perpetrator in Decision Number 27/Pid.Sus-Anak/2023/PN Smr and Decision Number 12/Pid.Sus-Anak/2024/PN Smr. The difference in punishment (criminal disparity) seen in both decisions can create a bad stigma in the eyes of the victim and the community, especially since both perpetrators committed crimes with a similar level of seriousness. This study aims to analyze the disparity that occurs between the two verdicts and analyze the judge's consideration in sentencing child offenders. This research uses a normative juridical method with qualitative analysis, and relates the theory of justice and juvenile punishment. The results of this study indicate that the disparity in punishment given is due to differences in the legal basis used so that the final punishment given in the two decisions is also different. This can be influenced by the different views of judges who, in making their decisions, are not only derived from juridical considerations but also non-juridical considerations.